(untitled) (Czech Journal of International Relations, 2003)
Timothy Edmunds - Anthony Foster - Andrew Cottey (eds.): The Challenge of Military Reform in Postcommunist Europe. Building the Professional Armed Forces. 1st ed. Palgrave, London 2002, 10 + 260 s., ISBN 0-333-94621-9.